Museum administration 2.0 - Genoways, Hugh H.; Ireland, Lynne M. 1953- (American Association for State and Local History book series, 2017)
"Wondering what a museum director actually does? About to start your first director's job? Looking for guidance in starting up a museum or working with a museum director? Hugh Genoways, Lynne Ireland, and Cinnamon Catlin-Legutko have taken the mystery out and put common sense and good guidance in. Learn about everything from budgets and strategic planning to human resources and facilities management to collections and programming. They also help you tackle legal documents, legal and ethical issues, and challenges for today's 2.0 world. Case studies and exercises throughout help you review and practice what you are learning, and their extensive references will be a welcome resource."--Provided by publisher.